2017
DOI: 10.1177/2058460117710682
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of a new iterative reconstruction algorithm for dose reduction in coronary artery calcium scoring

Abstract: Background: Coronary artery calcium (CAC) scoring is a widespread tool for cardiac risk assessment in asymptomatic patients and accompanying possible adverse effects, i.e. radiation exposure, should be as low as reasonably achievable. Purpose: To evaluate a new iterative reconstruction (IR) algorithm for dose reduction of in vitro coronary artery calcium scoring at different tube currents. Material and Methods: An anthropomorphic calcium scoring phantom was scanned in different configurations simulating slim, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For a method to be credible, it is crucial that the variability in measurement is as low as possible. There are several studies assessing the variability in CCS using identical machines, interscan variability, and ways to reduce this variability (7,8). McCollough et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a method to be credible, it is crucial that the variability in measurement is as low as possible. There are several studies assessing the variability in CCS using identical machines, interscan variability, and ways to reduce this variability (7,8). McCollough et al.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies assessing the variability in CCS using identical machines, interscan variability, and ways to reduce this variability (7,8). McCollough et al (9) reported the standardized quantification of coronary artery calcium results from equivalent calcium scores, acquired using different computed tomography (CT) systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 49% of coronary arteries, there was reduction in total Agatston scores with higher strength levels of IR. This phenomenon was reported in many studies [3,17,21,24]; and most likely caused as reported by Gassenmaier, et al and AlShammakhi & Sun [21,29] as a result of sharpening the calcifications and thus reducing the number of pixels with densities over the scoring threshold and thus suppressing the blooming artifacts and improve estimation of the true degree of luminal narrowing.…”
Section: Discussionmentioning
confidence: 66%
“…The Agatston score has been defined by Agatston and Janowitz and dates back into the 1980s [20]. This score still represents the most common established method for CCS quantification [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation